The role of individual differences and involvement on attitudes toward animal welfare - Powell, Gwendolen Mair (Kansas State University, 2010)
Previous research has indicated that many factors influence the likelihood of using the central or peripheral routes of processing during exposure to a persuasive message, including involvement in the message. Previous research has generally focused on response involvement, which is based on outcome, while the focus of the present study is involvement based on personal investment. In the present study, 229 undergraduates were assessed on their trait empathy toward animals, and attitudes toward animals. They read a strong or weak persuasive message presented by either an attractive or less attractive writer. This design replicated previous findings by Bae (2008) on empathy and attitude change, and extended them by examining them experimentally, with a focus on issue-based involvement, which relies on moral or ego involvement. Participants were tested on several distinct DVs designed to indicate their change in attitude and behavior. Results varied for each DV, with source attractiveness predicting willingness to wear a button and display a bumper sticker, but with trait empathy predicting willingness to adopt a pet and vote to support a petition. The results imply that participants relied on different routes of processing depending on the DV, and that the role of emotion in issue involvement may inform advertisers in ways to effectively increase the likelihood of paying attention to a message.
Keywords: persuasion; elaboration likelihood model; animals; animal welfare; Psychology, Cognitive (0633); Psychology, Social (0451)